GRK2 compromises cardiomyocyte mitochondrial function by diminishing fatty acid-mediated oxygen consumption and increasing superoxide levels. (December 2015) - Sato, Priscila Y.; Chuprun, J. Kurt; Ibetti, Jessica; Cannavo, Alessandro; Drosatos, Konstantinos; Elrod, John W.; Koch, Walter J.
Abstract: The G protein-coupled receptor kinase-2 (GRK2) is upregulated in the injured heart and contributes to heart failure pathogenesis. GRK2 was recently shown to associate with mitochondria but its functional impact in myocytes due to this localization is unclear. This study was undertaken to determine the effect of elevated GRK2 on mitochondrial respiration in cardiomyocytes. Sub-fractionation of purified cardiac mitochondria revealed that basally GRK2 is found in multiple compartments. Overexpression of GRK2 in mouse cardiomyocytes resulted in an increased amount of mitochondrial-based superoxide. Inhibition of GRK2 increased oxygen consumption rates and ATP production. Moreover, fatty acid oxidation was found to be significantly impaired when GRK2 was elevated and was dependent on the catalytic activity and mitochondrial localization of this kinase. Our study shows that independent of cardiac injury, GRK2 is localized in the mitochondria and its kinase activity negatively impacts the function of this organelle by increasing superoxide levels and altering substrate utilization for energy production. Highlights: Mitochondrial GRK2 is localized to multiple sub-mitochondrial locations. Overexpression of GRK2 in cardiomyocytes increases superoxide levels and impairs fatty acid-driven oxygen consumption rate. GRK2 kinase activity is necessary for the deleterious effect on mitochondrial energy dynamics. βARKct, a peptide inhibitor of GRK2, enhances basal oxygen consumption rates and ATP production.